2021
DOI: 10.3390/genes12081194
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the ASTN2 Locus in Cardiovascular, Metabolic and Psychiatric Traits: Evidence for Pleiotropy Rather Than Shared Biology

Abstract: Background: The link between cardiometabolic and psychiatric illness has long been attributed to human behaviour, however recent research highlights shared biological mechanisms. The ASTN2 locus has been previously implicated in psychiatric and cardiometabolic traits, therefore this study aimed to systematically investigate the genetic architecture of ASTN2 in relation to a wide range of relevant traits. Methods: Baseline questionnaire, assessment and genetic data of 402111 unrelated white British ancestry ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…RBM14-RBM4 is a member of this family and plays an important role in neuronal differentiation ( 37 ). ASTN2 is located on chromosome 9 and encodes a transmembrane protein that is mainly expressed in the brain ( 38 ). Through modulation of synaptic vesicle protein composition, ASTN2 facilitates glial-guided migration during brain development ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…RBM14-RBM4 is a member of this family and plays an important role in neuronal differentiation ( 37 ). ASTN2 is located on chromosome 9 and encodes a transmembrane protein that is mainly expressed in the brain ( 38 ). Through modulation of synaptic vesicle protein composition, ASTN2 facilitates glial-guided migration during brain development ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behesti et al ( 37 ) demonstrated that ASTN2 binds to and regulates the surface expression of multiple synaptic proteins in postmigratory neurons by endocytosis, resulting in the modulation of synaptic activity. In addition, by systematic analysis, Burt et al ( 38 ) found that ASTN2 has pleiotropic effects on cardiometabolic and psychiatric traits. However, ASTN2 role in AF remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, deletion in the ASTN2 gene results in a reversal of normal orientation of hair follicles in adult mice (parallel to "from head to tail") to the opposite direction (parallel to "from tail to head") (Chang et al, 2015). In humans, the ASTN2 gene is associated with the level of triglycerides in the blood (Jiao et al, 2015) and the development of obesity (Burt et al, 2021). Signatures of selection in this gene have been found in ethnic groups of southern Ethiopia, who have lived in high-altitude conditions for over a thousand years (Scheinfeldt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%